Praying with Paul : a call to spiritual reformation - Carson, D. A. (Grand Rapids, MI. Baker Academic., 2014)
Learning to pray like Paul. God doesn't demand hectic church programs and frenetic schedules; he only wants his people to know him more intimately. The apostle Paul found that spiritual closeness in his own fellowship with the Father. Praying with Paul calls believers to reject superficiality and revolutionize their lives by embracing a God-guided approach to prayer. By following Paul's life-shaping principles, we can hear God speak to us today. - Back cover.
Introduction: Neglected prayer -- Lessons from the school of prayer -- The framework of prayer: 2 Thessalonians 1:3-12 -- Worthy petitions: 2 Thessalonians 1:1-12 -- Praying for others -- A passion for people: 1 Thessalonians 3:9-13 -- The content of a challenging prayer: Colossians 1:9-14 -- Excuses for not praying -- Overcoming the hurdles: Philippians 1:9-11 -- A sovereign and personal God -- Praying to the sovereign God: Ephesians 1:15-23 -- Praying for power: Ephesians 3:14-21 -- Praying for ministry: Romans 15:14-33 -- Afterword: A prayer for spiritual reformation.
"First edition published in 1992 as A Call to Spiritual Reformation : priorities from Paul and his prayers"--Title page verso.
Includes bibliographical references and indexes.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Devotional use; Bible -- Prayers; Prayer -- Christianity